Public Speaking and Storytelling as Strategic Communication Competencies in Student Academic Competitions - Aditya Gilang Rumpaka (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2026)
The advancement of higher education in the contemporary era places students under a dual demand: to achieve academic excellence while simultaneously possessing communication competencies that actively support their performance in competitive events. This study examines the role of public speaking and storytelling in enhancing student performance in prestigious competitions, particularly the Outstanding Student Selection (Mawapres) and the Campus Ambassador program. A qualitative descriptive approach with a case study design was employed, and data were gathered through in-depth interviews with four purposively selected informants who had direct experience in such competitions. This study is conceptually grounded in the Narrative Transportation Theory (Green & Brock, 2000) and the Deliberate Practice Theory (Ericsson et al., 1993), which serve as the primary theoretical foundations for the research. Data analysis followed the Miles, Huberman, and Saldaña interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that public speaking reinforces structured, confident, and persuasive message delivery, while storytelling functions as a strategic communication instrument that cultivates emotional connection and sustains audience engagement. Both competencies operate synergistically: public speaking establishes the structural foundation, whereas storytelling amplifies impact and enhances message memorability. Students who had mastered both skills consistently demonstrated superior performance during jury presentations and selection processes. This study contributes theoretically to communication science by asserting that public speaking and storytelling are not merely technical skills but strategic communicative tools that directly shape academic achievement outcomes. Practically, the findings offer a foundation for designing integrated communication training programs within university student development units.